Effects of diluted methanol and water as foaming agents on the performance of latex foamed warm asphalt mixtures - Mohd Rosli Mohd Hasan; Tai Guo; Hainian Wang; Sharvin Poovaneshvaran; Ashiru Sani; Muhammad Khuzaimi Aziz; Seyed Reza Omranian (Journal of Traffic and Transportation Engineering (English ed. Online), 2023)
Latex as an asphalt modifier has gained popularity in the asphalt industry as it improves the durability of asphalt pavement. However, the elastomeric properties of latex stiffen the asphalt binders, resulting in additional energy consumption during the production of asphalt mixtures, which may cause a higher emission of greenhouse gases. This is undesirable for sustainable development and the environment. In this study, the applicability of diluted methanol and water was comparatively evaluated as foaming agents in the production of warm mix asphalt (WMA) mixtures incorporating latex. Diluted methanol was used because it has a lower boiling point and latent heat than water, allowing the asphalt mixture to be produced at a lower temperature and thus consuming less energy. The performance of the foamed asphalt mixture was investigated through service characteristics, mechanical performance, and moisture susceptibility of mixtures. The service characteristics, on the other hand, were measured in a laboratory while preparing and compacting the asphalt mixture, which refers to the amount of energy required during the production and construction stages in the asphalt plant and on the construction site, respectively. The degree of energy required was assessed based on the workability index, coatability index, and the compaction energy index. The mechanical performance of asphalt mixtures was characterized by indirect tensile strength, resilient modulus, and dynamic creep tests. The resistance to moisture damage was evaluated based on the common parameter, indirect tensile strength ratio. The findings revealed that the use of diluted methanol foaming agent helped improve the workability of latex modified asphalt mixtures. The foamed latex-modified WMA demonstrated better performance compared to asphalt mixtures prepared using water as the foaming agent.